Combining ecosystem indicators and life cycle assessment for environmental assessment of demersal trawling in Tunisia - Abdou, Khaled; François Le Loc’h, François; Gascuel, Didier; Romdhane, Mohamed Salah; Aubin, Joël; Lasram, Frida Ben Rais (Springer, 2019)
The approach consisted of conducting LCA and calculating ecosystem indicators to provide a complete assessment of trawling’s environmental impacts and the ecosystem characteristics associated with seafood production. The functional unit for the LCA was set to 1 t of landed seafood, and system boundaries included several operational stages related to demersal trawling. Several ecosystem indicators from EwE were calculated. Demersal trawling in the exploited ecosystem of the Gulf of Gabes (southern Tunisia) was used as a case study to illustrate the applicability of the approach. Several management plans were simulated and their influence on environmental performance was assessed. Ecospace, the spatial module of EwE, was used to simulate management scenarios: establishment of marine protected areas, extension of the biological rest period, and decrease in the number of demersal trawlers.
Keywords: Life cycle assessment; Fisheries; Ecosystem modeling; Ecopath with Ecosim; Ecospace; Demersal trawling; Environmental impacts; Gulf of Gabes